Negative electrode active material, negative electrode and battery

By using the chemical bonding of active particles of silicon and carbon elements to the coupling agent and metal compounds in the negative electrode active material of lithium-ion batteries to form a modified layer, the problem of volume expansion and low Coulomb efficiency in lithium-ion batteries is solved. Significantly improves the cycle life of the battery and the Coulomb efficiency.

CN114079051BActive Publication Date: 2024-12-27IND TECH RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202110947477.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-08-18
Filing Date
2021-08-18
Publication Date
2024-12-27
Estimated Expiration
2041-08-18

AI Technical Summary

Technical Problem

Silicon-based materials have short cycle life due to volume expansion and damage to solid electrolyte interface film in lithium-ion batteries, and the Coulombic efficiency of silicon oxide materials is low, which cannot meet the needs of high-capacity negative electrodes.

Method used

Using active particles containing silicon elements, carbon elements or combinations thereof, a modified layer is formed by chemical bonding of coupling agents to metal compound residues, thereby improving the stability and performance of the negative electrode active material, and combining conductive additives and adhesives to form a current collecting layer and An active material layer, used for the negative electrode of the battery.

Benefits of technology

The cycle life and Coulomb efficiency of lithium-ion batteries are significantly improved, achieving long battery life and efficient electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003217281400000061
    Figure BDA0003217281400000061
  • Figure BDA0003217281400000071
    Figure BDA0003217281400000071
Patent Text Reader

Abstract

The present invention relates to a negative electrode active material, a negative electrode and a battery. The negative electrode active material comprises active particles and a modified layer. The active particles contain silicon elements, carbon elements, or a combination thereof. The modified layer is coated on the surface of the active particles. The modified layer comprises a residue of a coupling agent and a residue of a metal compound. The residue of the coupling agent is bonded between the active particles and the residue of the metal compound. The residue of the metal compound contains a metal atom.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a negative electrode active material, a negative electrode and a battery. Background Art

[0002] As the energy density of lithium-ion batteries continues to increase, traditional graphite materials can no longer meet the design requirements of high-energy-density batteries. Silicon (Si)-based materials have become the most promising next-generation high-capacity negative electrode materials with a capacity of up to 4200mAh / g and a lithium-intercalation platform close to graphite. However, the volume expansion of silicon materials can reach more than 300% during the alloying process with lithium (Li), resulting in pulverization and fragmentation of particles, as well as destruction of the solid electrolyte interphase (SEI), which seriously affects the cycle life of lithium-ion batteries.

[0003] The emergence of silicon oxide (SiOx) materials has brought about a turning point in the application of high-capacity silicon-based negative electrodes. However, the coulombic efficiency of silicon oxide is much lower than that of graphite and silicon-carbon materials for the first time. This has become a major obstacle to the application of silicon oxide materials. Summary of the invention

[0004] The invention relates to a negative electrode active material, a negative electrode and a battery.

[0005] According to one aspect of the present invention, a negative electrode active material is proposed, which includes active particles and a modified layer; the active particles contain silicon elements, carbon elements, or a combination thereof; the modified layer is coated on the surface of the active particles; the modified layer contains residues of a coupling agent and residues of a metal compound; the residues of the coupling agent are bonded between the active particles and the residues of the metal compound; the residues of the metal compound contain metal atoms.

[0006] According to another aspect of the present invention, a negative electrode is provided, which comprises a current collecting layer and an active material layer; the active material layer is on the current collecting layer; the active material layer comprises the negative electrode active material as described above, a conductive additive and a binder.

[0007] According to another aspect of the present invention, a battery is provided, which comprises a positive electrode, the negative electrode as described above, a separator and an electrolyte; the separator is between the positive electrode and the negative electrode; and the electrolyte is between the positive electrode and the negative electrode.

[0008] In order to have a better understanding of the above and other aspects of the present invention, the following embodiments are specifically described in detail as follows. Implementation

[0009] According to the embodiments of the present disclosure, a negative electrode active material, a negative electrode and a battery using the negative electrode active material are provided, and the battery has a longer cycle life and better coulombic efficiency.

[0010] According to an embodiment of the present disclosure, the negative electrode active material may include active particles and a modified layer.

[0011] The active particles (negative electrode active particles) contain silicon, carbon, or a combination thereof. The active particles may include silicon (Si), silicon oxide (SiOx), carbon-modified silicon oxide, silicon carbon (SiC), carbon material (carbon material), or a combination thereof. Carbon materials include, for example, natural graphite, artificial graphite, soft carbon, hard carbon, graphene, or graphitized carbon fiber.

[0012] The modified layer is coated on the surface of the active particle, and the modified layer includes the residue of the coupling agent and the residue of the metal compound. According to an embodiment of the present disclosure, there is a chemical bond between the modified layer and the surface of the active particle, wherein the residue of the coupling agent is bonded between the active particle and the residue of the metal compound. The residue of the metal compound contains a metal atom, for example, lithium (Li), sodium (Na), potassium (K), or a combination thereof.

[0013] The coupling agent may be a silane compound. In the chemical structure of the silane compound, the substituent on the silicon atom (e.g., the first reactive substituent) is a hydrolyzable group or a methyl group, and the other substituent (e.g., the second reactive substituent) is a group containing a thiol (-SH), epoxy, vinyl, or amine group.

[0014] The silane compound can be represented by formula (1):

[0015] Q m H 3-m SiA formula (1)

[0016] Wherein, Q (hereinafter referred to as the first reactive substituent) is independently a hydrolyzable group or a methyl group; m=1 to 3; A (hereinafter referred to as the second reactive substituent) is a group containing a thiol (-SH), epoxy, vinyl, or amine group at the end. The aforementioned hydrolyzable group may be an alkoxy group, which can be represented by -OR, and R represents an alkyl group with a carbon number of 1 to 5. In some embodiments, the aforementioned hydrolyzable group includes a methoxy group (-OCH3) or an ethoxy group (-OCH2CH3). In some embodiments, the aforementioned group containing a thiol (-SH), epoxy, vinyl, or amine group at the end may include an alkylene group with a carbon number of 1 to 8. For example, the group containing a thiol (-SH) group may be -(CH2) n -SH, n=1~8.

[0017] The coupling agent may include 3-mercaptopropyltrimethoxysilane (MPTMS), 3-mercaptopropylmethyldimethoxysilane (MPDMS), 3-glycidoxypropyltrimethoxysilane (GPTMS), 3-aminopropyltrimethoxysilane (APTMS), 3-aminopropyltriethoxysilane (APTES), or a combination thereof.

[0018] In some embodiments, the aforementioned metal compound may include a metal hydroxide or a lithium compound. The metal atom of the metal hydroxide may include lithium (Li), sodium (Na), potassium (K), or a combination thereof. The metal hydroxide includes sodium hydroxide (NaOH), lithium hydroxide (LiOH), potassium hydroxide (KOH), or a combination thereof. The lithium compound includes lithium carbonate (Li2CO3), lithium bicarbonate (LiHCO3), lithium sulfide (Li2S), lithium carbide (Li2C2), lithium dihydrogen phosphate (LiH2PO4), or a combination thereof.

[0019] In some embodiments, the method for preparing the aforementioned negative electrode active material may include the following steps. First, the aforementioned coupling agent and the aforementioned active particles are mixed to obtain a first mixture. The first reactive substituent (hydrolyzable group) of the coupling agent may form a bond with the active particle. For example, silicon oxide (active particle) may contain a hydroxyl group. The hydrolyzable group of the coupling agent may form a bond with the hydroxyl group (-OH) on the surface of the active particle after a hydrolysis reaction. For example, the hydrolyzable group of the coupling agent may form a bond with the hydroxyl group on the surface of the active particle after a dehydration condensation reaction. The residue left after the coupling agent in the first mixture reacts with the active particle may contain a second reactive substituent (a group comprising a thiol, epoxy, vinyl, or amine group), that is, the second reactive substituent may not react with the active particle and remain in the residue. In some embodiments, the weight of the coupling agent is 0.1% to 2% of the weight of the active particle.

[0020] Then, the first mixture is mixed with the aforementioned metal compound to obtain a second mixture. The second reactive substituent (including a thiol, epoxy, vinyl, or amine group) contained in the residue of the coupling agent in the first mixture can form a bond with the metal compound. For example, the second reactive substituent of the coupling agent can form a hydrogen bond with the metal compound. For example, the second reactive substituent of the coupling agent can form a bond with the metal compound after a hydrolysis reaction. For example, the second reactive substituent of the coupling agent can form a bond with the metal compound after a dehydration condensation reaction. The metal compound residue left after the metal compound reacts with the coupling agent residue to form a bond contains a metal atom. In some embodiments, the weight of the coupling agent: the weight of the metal compound is 1:1 to 1:10. After the above reaction is completed, the aforementioned negative electrode active material can be obtained, that is, the negative electrode active material includes active particles and a modified layer, and the modified layer is coated on the surface of the active particles; the modified layer includes the residue of the coupling agent and the residue of the metal compound, and the residue of the coupling agent is bonded between the active particle and the residue of the metal compound, and the residue of the metal compound contains a metal atom. In an embodiment, the first mixture may be mixed with a solution of a metal compound to obtain a second mixture. The solution of the metal compound includes the metal compound and a solvent. The solvent may include water (e.g., deionized water). The solution of the metal compound may be an aqueous solution containing the metal compound.

[0021] In some embodiments, the negative electrode active material can be used as a negative electrode of a battery.

[0022] The battery provided by the present disclosure includes a negative electrode, a positive electrode, a separator and an electrolyte. The separator is arranged between the positive electrode and the negative electrode to separate the positive electrode and the negative electrode; a containing space is defined between the positive electrode and the negative electrode, and the electrolyte is arranged in the containing space and between the positive electrode and the negative electrode.

[0023] The negative electrode of the battery includes a collector layer and an active material layer. The active material layer is disposed on the collector layer, and the active material layer includes a negative electrode active material, a conductive additive, and an adhesive. The active material layer may be formed by a negative electrode active material slurry (or a negative electrode active material slurry composition). The negative electrode active material slurry includes a negative electrode active material, a conductive additive, and an adhesive. The conductive additive may include carbon black, conductive graphite, carbon nanotubes, carbon fiber, graphene, or a combination thereof. The adhesive may include polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), polyacrylic acid (PAA), or polyacrylonitrile (PAN), polyethylene glycol (PEG), carboxymethyl cellulose (CMC), polyethylene oxide (PEO), or a combination thereof. The collector layer may include a metal, such as a copper sheet.

[0024] The positive electrode of the battery comprises a positive electrode active material, which comprises lithium cobalt oxide (LCO), lithium nickel cobalt manganese oxide (NMC), lithium nickel cobalt aluminum oxide (NCA), lithium iron phosphate (eg LiFePO4, referred to as LFP), or a combination thereof.

[0025] The aforementioned isolation film may include polyethylene (PE), polypropylene (PP), aramid, ceramic, or a combination thereof.

[0026] The electrolyte may include a lithium salt, a solvent, and an acrylic resin. The solvent may be propylene carbonate, ethylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, fluoroethylene carbonate, or a combination thereof.

[0027] In order to make the above-mentioned purposes, features, and advantages of the present disclosure more clearly understood, specific embodiments are given below for detailed description as follows:

[0028] <Example 1>

[0029] Based on the weight of the solid content of the negative electrode active material slurry, 0.2 weight % (wt %) of 3-thiolpropyltrimethoxysilane as a coupling agent, 96.05 weight % of active particles SiO / C (a mixture of silicon oxide and carbon material, brand name BTR-SiO550-1A), and 0.30 weight % of conductive additive Super-p (carbon black) are uniformly mixed to obtain a first mixture. Then, a LiOH aqueous solution with a concentration of 5 weight % to 10 weight % is added to the first mixture, and the amount of LiOH in the LiOH aqueous solution is 0.2 weight % of the active particles (SiO / C) to obtain a second mixture, and the mixture is stirred and mixed at 45°C for 120 minutes for pre-reaction treatment by hydration method. In this way, the prepared second mixture contains the negative electrode active material: surface-modified SiO / C particles. Then, the negative electrode active material (containing surface-modified SiO / C particles) and the conductive carbon liquid CNT (brand name: TUBALL) with a solid content of 0.495 wt % based on the solid content of the negative electrode active material slurry were added. TM , containing carbon nanotubes, purchased from OCSiAl), electrode adhesive CMC with a solid content of 1.28 wt%, SBR with a solid content of 1.48 wt%, etc. are dispersed in deionized water to form a negative electrode active material slurry with a uniform structure (solid content of about 43 wt%), which is coated on the metal copper sheet collector layer to obtain a negative electrode plate.

[0030] Based on the weight of the solid content of the positive electrode active material slurry, 97.3 wt % of NMC811, 1 wt % of Super-p, 1.4 wt % of PVDF5130, and 0.3 wt % of CNT were uniformly dispersed in N-methylpyrrolidone (NMP) solvent to form a positive electrode active material slurry with a uniform structure (solid content of about 70 wt %), which was coated on the metal aluminum sheet collector layer to obtain a positive electrode plate.

[0031] The negative electrode plate, the positive electrode plate and the separator are assembled into a standard battery core (Jelly Roll) with a size of 65mm (height) x 60mm (width) x 70mm (length), that is, a 656070 standard battery core, and 16.5 grams of liquid standard electrolyte is poured into it, and a lithium-ion secondary battery is obtained after packaging.

[0032] <Example 2>

[0033] The manufacturing method of the lithium ion secondary battery of Example 2 is similar to that of Example 1, except that during the preparation of the negative electrode active material slurry, the amount of LiOH in the LiOH aqueous solution is 0.3 wt % of the active particles SiO / C.

[0034] <Example 3>

[0035] The manufacturing method of the lithium ion secondary battery of Example 3 is similar to that of Example 1, except that during the preparation of the negative electrode active material slurry, the amount of LiOH in the LiOH aqueous solution is 0.4 wt % of the active particles SiO / C.

[0036] <Example 4>

[0037] The manufacturing method of the lithium-ion secondary battery of Example 4 is similar to that of Example 2, except that during the preparation of the negative electrode active material slurry, the LiOH aqueous solution is replaced by a KOH aqueous solution, the amount of KOH in the KOH aqueous solution is 0.3 wt % of the active particles SiO / C, and the second mixture is pre-reacted by stirring and mixing at 45° C. for 60 minutes using a hydration method.

[0038] <Example 5>

[0039] The manufacturing method of the lithium-ion secondary battery of Example 5 is similar to that of Example 1, except that in the preparation process of the negative electrode active material slurry, the added amount of active particles SiO / C (a mixture of silicon oxide and carbon material, brand name BTR-SiO550-1A) is 96.29 weight % (based on the weight of the solid content of the negative electrode active material slurry); the amount of LiOH in the LiOH aqueous solution is 1 weight % of the active particles SiO / C; and the second mixture is pre-reacted by stirring and mixing at 45°C for 60 minutes using a hydration method.

[0040] <Example 6>

[0041] The manufacturing method of the lithium ion secondary battery of Example 6 is similar to that of Example 5, except that in the preparation process of the negative electrode active material slurry, 3-aminopropyltriethoxysilane (APTES) is used as a coupling agent; and the amount of LiOH in the LiOH aqueous solution is 0.2 wt % of the active particles SiO / C.

[0042] <Comparative Example 1>

[0043] The manufacturing method of the lithium ion secondary battery of Comparative Example 1 is similar to that of Example 1, except that the negative electrode active material uses SiO / C particles without surface modification.

[0044] <Comparative Example 2>

[0045] The manufacturing method of the lithium ion secondary battery of Comparative Example 2 is similar to that of Comparative Example 1, except that Comparative Example 2 uses a LiOH aqueous solution with a concentration of 0.2 wt % and does not use any coupling agent.

[0046] <Evaluation>

[0047] Table 1 lists the coulombic efficiencies of the lithium-ion secondary batteries of Examples 1 to 6 and Comparative Examples 1 to 2 measured by a 0.1C charge and 0.1C discharge cycle, and the capacity retention rates (calculated as a percentage based on the maximum storage capacity) at the 400th and 800th charge and discharge cycle test cycles by a 0.5C charge and 0.5C discharge cycle. Table 1

[0048]

[0049]

[0050] From the test data, it can be seen that compared with the battery of the comparative example without the surface-modified SiO / C particles, the battery of the embodiment with the surface-modified SiO / C particles has a longer cycle life and better coulombic efficiency, including better first (first) coulombic efficiency. In addition, the capacity retention rates of Example 1 and Example 2 at the 800th cycle are 87.6% and 87.2%, respectively, which are significantly better than the capacity retention rates of 78.4% and 74.5% of Comparative Example 1 and Comparative Example 2 at the 400th cycle.

[0051] In summary, although the present invention has been disclosed in the above embodiments, it is not intended to limit the present invention. Those skilled in the art of the present invention may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be determined by the attached claims.

Claims

1. Negative electrode active material, comprising: Active particles containing silicon, carbon, or a combination thereof; and A modification layer is coated on the surface of the active particle, wherein the modification layer comprises a residue of a coupling agent and a residue of a metal compound, the residue of the coupling agent is bonded between the active particle and the residue of the metal compound, and the residue of the metal compound contains a metal atom, The coupling agent is a silane compound represented by formula (1): Q m H 3-m SiA formula (1) in, m=1~3, Q is each independently a hydrolyzable group or a methyl group, A is a group containing a thiol group (-SH) at the terminal, The metal compound comprises a metal hydroxide, and the metal hydroxide comprises sodium hydroxide, lithium hydroxide, potassium hydroxide, or a combination thereof. 2 . The negative electrode active material as claimed in claim 1 , wherein the active particles comprise silicon, silicon oxide, carbon-modified silicon oxide, silicon carbon, carbon material, or a combination thereof. The negative electrode active material according to claim 1 , wherein the hydrolyzable group is an alkoxy group. 4 . The negative electrode active material of claim 1 , wherein the coupling agent comprises 3-thiolpropyltrimethoxysilane, 3-thiolpropylmethyldimethoxysilane, or a combination thereof. 5 . The negative electrode active material of claim 1 , wherein the metal atom comprises lithium, sodium, potassium, or a combination thereof.

6. Negative electrode, including: a current collecting layer; and An active material layer is on the current collecting layer and comprises the negative electrode active material as claimed in claim 1, a conductive additive, and a binder. 7 . The negative electrode of claim 6 , wherein the conductive additive comprises carbon black, conductive graphite, carbon nanotubes, carbon fibers, graphene, or a combination thereof. 8 . The negative electrode of claim 6 , wherein the binder comprises polyvinylidene fluoride, styrene-butadiene rubber, polyacrylic acid, polyacrylonitrile, polyethylene glycol, carboxymethyl cellulose, polyethylene oxide, or a combination thereof.

9. The negative electrode of claim 6, wherein the current collecting layer comprises a copper sheet.

10. Batteries, including: positive electrode; The negative electrode as claimed in claim 6; a separator between the positive electrode and the negative electrode; and An electrolyte is between the positive electrode and the negative electrode.

11. The battery of claim 10, wherein the positive electrode comprises a positive electrode active material comprising lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, or a combination thereof.